Negative electrode material, secondary battery and electric equipment

By matching the G-peak half-maximum width and powder compaction density of the negative electrode material in the lithium-ion secondary battery, the problem of difficult balance between high capacity and high compaction of the secondary battery is solved, and high energy density and excellent cycling performance are achieved.

CN119786597AActive Publication Date: 2025-04-08SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411985606.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Existing lithium-ion secondary batteries are difficult to balance between high capacity and high compaction, resulting in insufficient kinetic performance and cycle life.

Method used

By matching the relationship between the G-peak half-maximum width of the negative electrode material and the powder compaction density, a secondary battery with high capacity, high compaction, high energy density and excellent circulation performance was prepared.

Benefits of technology

The high energy density and excellent cycle performance of the secondary battery are achieved, with a gram capacity of more than 354mAh/g, a cycle number of more than 1200, and a capacity retention rate of more than 85% at a 4C ratio.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005222584500000091
    Figure BDA0005222584500000091
  • Figure BDA0005222584500000101
    Figure BDA0005222584500000101
  • Figure BDA0005222584500000121
    Figure BDA0005222584500000121
Patent Text Reader

Abstract

The invention provides a negative electrode material, a secondary battery and electric equipment. According to the present invention, the relationship between the half peak width of the G peak of the negative electrode material and the powder compaction density of the negative electrode material powder under the pressures of 3T and 5T is matched so as to prepare the high-capacity and high-compaction secondary battery; the negative electrode material comprises a carbonaceous material and meets the following relational expression: 12.0 < = 2 * (Y-Q) + 1.5 * Gh < = 60.5; gh cm <-1 > represents the half-peak width of a G peak of the negative electrode material at the position with the displacement of 1580 + / -10 cm <-1 > in a Raman spectrum; y g / cm < 3 > represents the powder compaction density of the negative electrode material under the pressure of 5T; q g / cm < 3 > represents the powder compaction density of the negative electrode material under the pressure of 3T. And the gram capacity of the negative electrode material is more than 354 mAh / g, and when the obtained battery circulates at 45 DEG C and 1C / 1C, the number of circulation turns is more than 1200 when the capacity retention rate reaches 80%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, in particular to a negative electrode material, a secondary battery and an electrical device. Background Art

[0002] Lithium-ion secondary batteries have been widely used in many industries due to their advantages such as high energy / power density, long cycle life and no pollution. Among them, graphite is still the mainstream negative electrode material for lithium-ion secondary batteries. Sulfur-containing coke is usually used as raw material for preparing graphite. According to the sulfur content in the raw materials, it can be divided into low-sulfur coke, medium-sulfur coke and high-sulfur coke, among which high-sulfur coke raw materials account for the majority (~40%). Using high-sulfur coke as raw material can ensure the supply problem on the raw material side, and the capacity of high-sulfur coke is higher than that of low-sulfur coke, but the high sulfur content leads to higher internal porosity and lower material compaction density. Therefore, balancing the high capacity and high compaction of secondary batteries prepared with high-sulfur coke as raw material is the current technical development difficulty. Summary of the invention

[0003] The purpose of the present application is to provide a negative electrode material, a secondary battery and an electrical device to improve the capacity, energy density and cycle performance of the battery.

[0004] To achieve the above object, in a first aspect of the present application, a negative electrode material is provided, wherein the negative electrode material comprises a carbonaceous material, and the negative electrode material satisfies the following relationship:

[0005] 12.0≤2×(YQ)+1.5×Gh≤60.5

[0006] Where, Gh cm -1 Indicates that the negative electrode material has a displacement of 1580±10cm in the Raman spectrum -1 The half-peak width of the G peak at position;

[0007] Y g / cm 3 Indicates the powder compaction density of the negative electrode material under a pressure of 5T;

[0008] Q g / cm 3 It represents the powder compaction density of the negative electrode material under a pressure of 3T.

[0009] As an embodiment of the present application, the negative electrode material satisfies the following relationship: 20.0≤2×(YQ)+1.5×Gh≤50.0.

[0010] As an embodiment of the present application, the half peak width Gh of the negative electrode material in the Raman spectrum satisfies: 8 cm -1 ≤Gh≤40cm -1 .

[0011] As an embodiment of the present application, the powder compaction density Y of the negative electrode material under a pressure of 5T satisfies: 1.800 g / cm 3 ≤Y≤1.900g / cm 3 .

[0012] As an embodiment of the present application, the powder compaction density Q of the negative electrode material under a pressure of 3T satisfies: 1.600 g / cm 3 ≤Q≤1.700g / cm 3 .

[0013] As an embodiment of the present application, the specific surface area BET of the negative electrode material satisfies: 0.5 m 2 / g≤BET≤2.7m 2 / g.

[0014] As an embodiment of the present application, the graphitization degree of the negative electrode material is G, which satisfies: 92%≤G≤95%.

[0015] As an embodiment of the present application, when the cumulative volume of the negative electrode material reaches 90%, the corresponding particle size is D V 90, satisfying: 20μm≤D V 90≤50μm.

[0016] As an embodiment of the present application, when the cumulative volume of the negative electrode material reaches 50%, the corresponding particle size is D V 50, satisfying: 10μm≤D V 50≤20μm.

[0017] As an embodiment of the present application, when the volume of the negative electrode material reaches 10%, the corresponding particle size is D V 10, meet: 5μm≤D V 10≤12μm.

[0018] As an embodiment of the present application, the negative electrode material satisfies: 1.5≤(D V 90-D V 10) / D V 50≤2.0.

[0019] As an embodiment of the present application, the gram capacity of the negative electrode material is ≥354 mAh / g.

[0020] As an embodiment of the present application, the sulfur content of the negative electrode material is ≤0.01 wt %.

[0021] In a second aspect of the present application, a secondary battery is provided, which comprises a positive electrode plate, an electrolyte, a separator and a negative electrode plate; the negative electrode plate comprises a negative electrode collector and a negative electrode active material layer arranged on at least one surface of the negative electrode collector, and the negative electrode active material layer contains the negative electrode material described in the first aspect of the present application.

[0022] A third aspect of the present application provides an electrical device, wherein the electrical device comprises the secondary battery described in the second aspect of the present application.

[0023] Compared with the prior art, the beneficial effects of this application are:

[0024] The present application prepares a secondary battery with high capacity and high compaction by matching the relationship between the G peak half-width of the negative electrode material and the compaction density of the negative electrode material powder under 3T and 5T pressures. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0026] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0027] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0028] The reagents or instruments used in this application without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0029] In a first aspect of the present application, a negative electrode material is provided, wherein the negative electrode material comprises a carbonaceous material, and the negative electrode material satisfies the following relationship:

[0030] 12.0≤2×(YQ)+1.5×Gh≤60.5

[0031] Where, Gh cm-1 Indicates that the negative electrode material has a displacement of 1580±10cm in the Raman spectrum -1 The half-peak width of the G peak at position;

[0032] Y g / cm 3 Indicates the powder compaction density of the negative electrode material under a pressure of 5T;

[0033] Q g / cm 3 It represents the powder compaction density of the negative electrode material under a pressure of 3T.

[0034] The present application prepares a secondary battery with high capacity and high compaction by matching the relationship between the G peak half-width of the negative electrode material and the compaction density of the negative electrode material powder under 3T and 5T pressures.

[0035] Gh represents the negative electrode material at 1580 cm in the Raman spectrum. -1 The half-peak width of the G peak nearby. The G peak is an important characteristic peak in the Raman spectrum of carbon materials, generally appearing at about 1580cm -1 Nearby, it reflects the carbon atom sp 2 The vibration mode in the hybrid state, and its specific position and shape (including half-peak width) can provide information about the structure and quality of the material; the half-peak width (FWHM) of the G peak is usually used in Raman spectroscopy to characterize properties such as the internal defect density of the material. It is related to the defect concentration and disorder of the carbonaceous material in the negative electrode material. The greater the disorder, the higher the lattice defect concentration in the negative electrode material. The defect concentration of the carbonaceous material will affect the rate of lithium ion migration in the solid phase inside it, thereby affecting the kinetic performance of the secondary battery, especially the first effect and cycle life; the powder compaction density of the negative electrode material has a certain influence on the porosity of the negative electrode sheet and the battery performance. Generally, the greater the powder compaction density, the denser the negative electrode active material layer and the smaller the porosity, the closer the negative electrode active material particles will be, and the energy density will be higher, but it is not conducive to the infiltration of the electrolyte, and the diffusion rate of the liquid phase is affected, thereby further affecting the battery's cycle performance. The present application has found through a large number of experimental studies that by controlling the half-peak width of the G peak of the negative electrode material and the powder compaction density of the negative electrode material powder under pressures of 3T and 5T, so that the three meet a specific relationship, a secondary battery with high capacity, high compaction, high energy density and excellent cycle performance can be prepared.

[0036] When the negative electrode material satisfies 12.0≤2×(YQ)+1.5×Gh≤60.5, the kinetic performance of the secondary battery is better. Exemplarily, the value of the relationship can be any one of 12.400, 15.390, 22.870, 27.366, 30.360, 37.870, 42.366, 45.352, 48.364, 52.846, 54.344, 58.880, 60.378 or a range between any two values. In some embodiments, the negative electrode material satisfies the following relationship: 20.0≤2×(YQ)+1.5×Gh≤50.0.

[0037] In some embodiments, the half-peak width Gh of the negative electrode material in the Raman spectrum satisfies: 8 cm -1 ≤Gh≤40cm -1 For example, the half-peak width Gh may be 8 cm -1 、10cm -1 、15cm -1 、18cm -1 , 20cm -1 、25cm -1 、28cm -1 、30cm -1 、35cm -1 、37cm -1 、40cm -1 Any value or a range of values ​​between any two values.

[0038] In some embodiments, the powder compaction density Y of the negative electrode material under a pressure of 5T satisfies: 1.800 g / cm 3 ≤Y≤1.900g / cm 3 For example, the value of Y can be 1.808 g / cm 3 、1.81g / cm 3 , 1.817g / cm 3 , 1.834g / cm 3 , 1.840g / cm 3 , 1.853g / cm 3 , 1.860g / cm 3 , 1.870g / cm 3 、1.875g / cm 3 , 1.890g / cm 3 , 1.900g / cm 3 Any value or a range of values ​​between any two values.

[0039] In some embodiments, the powder compaction density Q of the negative electrode material under 3T pressure satisfies: 1.600 g / cm3 ≤Q≤1.700g / cm 3 For example, the value of Q can be 1.619 g / cm 3 , 1.624g / cm 3 , 1.645g / cm 3 , 1.652g / cm 3 , 1.670g / cm 3 , 1.675g / cm 3 , 1.682g / cm 3 , 1.687g / cm 3 , 1.695g / cm 3 , 1.700g / cm 3 Any value or a range between any two values ​​in . Appropriate powder compaction density can reduce the internal resistance of the pole piece and reduce the polarization loss, which is beneficial to prolonging the cycle life of the prepared secondary battery.

[0040] In some embodiments, the specific surface area BET of the negative electrode material satisfies: 0.5 m 2 / g≤BET≤2.7m 2 / g. The specific surface area of ​​the negative electrode material mainly affects the formation of the negative electrode SEI film, and then affects the dynamic performance of the secondary battery. The specific surface area of ​​the negative electrode material within the above-mentioned appropriate range can reduce the capacity loss caused by the reaction between the negative electrode material and the electrolyte in the secondary battery, and can also reduce the possibility of lithium precipitation under high-rate current cycling, which can further improve the dynamic performance of the prepared secondary battery. For example, the specific surface area BET value of the negative electrode material can be 0.98m 2 / g, 1.15m 2 / g, 1.25m 2 / g, 1.30m 2 / g, 1.40m 2 / g, 1.54m 2 / g, 1.68m 2 / g, 1.95m 2 / g, 2.31m 2 Any value or a range between any two values ​​in / g.

[0041] In some embodiments, the graphitization degree of the negative electrode material is G, which satisfies: 92% ≤ G ≤ 95%. As the name implies, the graphitization degree is the degree of closeness between the crystal structure of the negative electrode material and the complete layered structure of the ideal graphite. The higher the graphitization degree, the higher the degree of ordering of the negative electrode material at the microscopic level, the fewer defects such as stacking faults and dislocations in the crystal, the higher the corresponding gram capacity, and the higher the energy density of the secondary battery; however, as the graphitization degree of the negative electrode material increases, the solid phase conduction of the active ions is affected, the more difficult it is for the active ions to enter and exit, the poorer the kinetic performance of the secondary battery, especially the high rate charge and discharge of the secondary battery. Therefore, the graphitization degree of the negative electrode material is within the above-mentioned appropriate range, which can ensure that the secondary battery has both high energy density and high rate cycle performance. Exemplarily, the value of G can be any one of 92.0%, 92.5%, 93.0%, 93.5%, 93.8%, 94.5%, 95.0%, or a range value between any two values.

[0042] In addition, the particle size and particle size distribution of the negative electrode material within a suitable range helps to increase the compaction density of the negative electrode sheet, thereby improving the volume energy density of the secondary battery. The particle size of the negative electrode material within a suitable range helps to embed and extract active ions, save conduction time, and have better charge and discharge performance.

[0043] In some embodiments, when the volume of the negative electrode material reaches 90%, the corresponding particle size is D V 90, satisfying: 20μm≤D V 90≤50μm. Exemplarily, the D V The value of 90 can be any one of 27.8μm, 28.5μm, 29μm, 29.5μm, 30.2μm, 31.5μm, 32μm, 32.5μm, 32.8μm, 33.8μm, 44.0μm, 45.0μm, 48.0μm, or a range between any two values.

[0044] In some embodiments, when the volume of the negative electrode material reaches 50%, the corresponding particle size is D V 50, satisfying: 10μm≤D V 50≤20μm. Exemplarily, the D V The value of 50 can be any one of 12.5μm, 12.9μm, 13.2μm, 13.6μm, 14.0μm, 14.2μm, 15.0μm, 16.5μm, 17.0μm, 18.0μm, or a range between any two values.

[0045] In some embodiments, when the volume of the negative electrode material reaches 10%, the corresponding particle size is D V 10, meet: 5μm≤DV 10≤12μm. Exemplarily, the D V The value of 10 can be any one of 6.2μm, 6.6μm, 6.8μm, 7.2μm, 7.6μm, 7.9μm, 8.2μm, 10.0μm, 10.4μm, 11.5μm, or a range between any two values.

[0046] In some embodiments, the particle concentration of the negative electrode material (also referred to as K90) satisfies: 1.5≤K90=(D V 90-D V 10) / D V 50≤2.0. The particle concentration can reflect the particle size distribution of the powder material. When the particle size distribution of the powder particles of the negative electrode material satisfies the above relationship, the smaller particles in the system can fill the gaps between the larger particles, which helps to increase the compaction density of the negative electrode sheet, thereby improving the volume energy density of the prepared secondary battery. Reasonable particle size distribution can not only improve the compaction density of the secondary battery but also improve the cycle performance of the secondary battery. Exemplarily, the value of K90 can be any one of 1.51, 1.53, 1.58, 1.64, 1.76, 1.86, 1.90, 1.96, 2.03, 2.04, 2.06 or a range between any two values.

[0047] The improvement of the gram capacity of the negative electrode material is a key contributing factor to improving the energy density of lithium-ion secondary batteries. The gram capacity of the negative electrode material prepared in this application is above 354 mAh / g, which can meet the use requirements of secondary batteries.

[0048] The sulfur content of the negative electrode material prepared in the present application is within 0.01wt%.

[0049] It should be noted that the negative electrode material described in the present application is prepared with high-sulfur coke as raw material through a front-end high-temperature rearrangement reaction. The use of high-sulfur coke as raw material can not only alleviate the shortage of low-sulfur coke resources, but also achieve cost reduction on the raw material side, and further regulate the G peak half-width of the negative electrode material and the powder compaction density of the negative electrode material powder under 3T and 5T pressures to meet a specific relationship, so as to prepare a secondary battery with high capacity, high energy density and cycle performance.

[0050] In some embodiments, the sulfur content in the high-sulfur coke is in the range of 3% to 7%.

[0051] In some embodiments, the specific process of the front-end high temperature rearrangement reaction is:

[0052] A petroleum coke raw material with a sulfur content of 3% to 7% is selected, heated at a low temperature of 600°C to 900°C for 4 to 6 hours for shallow calcination, and then crushed and dried to obtain a coarse powder; the coarse powder is placed in a high-temperature furnace and heated to 2700 to 3000°C at a heating rate of 5 to 15°C / min under an argon inert atmosphere for high-temperature graphitization treatment for 20 to 24 hours to obtain a single-particle graphitized product, and the obtained single-particle graphitized product is sieved and demagnetized to obtain a finished product.

[0053] In a second aspect of the present application, a secondary battery is provided, which comprises a positive electrode plate, an electrolyte, a separator and a negative electrode plate; the negative electrode plate comprises a negative electrode collector and a negative electrode active material layer arranged on at least one surface of the negative electrode collector, and the negative electrode active material layer contains the negative electrode material described in the first aspect of the present application.

[0054] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer contains a negative electrode active material.

[0055] The types of the negative electrode current collector and the positive electrode current collector are not specifically limited and can be selected according to actual needs.

[0056] In some embodiments, the negative electrode current collector may preferably use copper foil or carbon-coated copper foil, etc.; the positive electrode current collector may include but is not limited to metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, etc.; carbon materials such as carbon cloth and carbon paper; composite materials formed by polymers and metal layers. In some embodiments, the positive electrode current collector preferably uses aluminum foil.

[0057] In the present application, the type of positive electrode active material is not limited and can be selected according to actual needs. For example, the positive electrode active material can be lithium iron phosphate, lithium iron manganese phosphate, or a ternary positive electrode material. The positive electrode active material may also contain doping elements and / or coating elements. There are no special requirements for the doping elements and / or coating elements, as long as they can make the positive electrode active material more stable.

[0058] In addition, the negative electrode active material layer and the positive electrode active material layer further contain at least one of a conductive agent, a binder, and a thickener.

[0059] Commonly used battery conductive agents, binders and thickeners in the art can be used in this application.

[0060] In some embodiments, the conductive agent includes but is not limited to at least one of graphite, carbon black, acetylene black, Ketjen black, carbon nanotubes, and graphene.

[0061] In some embodiments, the binder includes but is not limited to at least one of styrene-butadiene rubber, polyacrylic acid, polyacrylonitrile, polyvinylidene fluoride, vinylidene fluoride-tetrafluoroethylene copolymer, and vinylidene fluoride-hexafluoropropylene copolymer.

[0062] In some embodiments, the thickener includes but is not limited to at least one of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose.

[0063] In some embodiments, the type of solvent used to form the positive electrode slurry and / or the negative electrode slurry is not limited, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the negative electrode active material, the conductive agent, the binder, and the dispersant.

[0064] In the secondary battery described in the present application, the type of the separator is not particularly limited and can be selected according to actual needs. The separator can be a polypropylene film, a polyethylene film, a polyvinylidene fluoride, a spandex film, an aramid film, or a multilayer composite film modified by a coating.

[0065] In the secondary battery described in the present application, the type of electrolyte is not particularly limited and can be selected according to actual needs.

[0066] In some embodiments, the preparation of a secondary battery includes: stacking the positive electrode sheet, the isolation membrane, and the negative electrode sheet in order, so that the isolation membrane is between the positive and negative electrode sheets to play an isolating role, and then winding them into a square bare cell, loading them into a battery casing, and then baking them at 65 to 95°C to remove water, injecting electrolyte, sealing, and obtaining a secondary battery after standing, hot and cold pressing, formation, clamping, capacity division and other processes.

[0067] The third aspect of the present application provides an electric device, which includes the secondary battery described in the second aspect of the present application. The electric device can be an application device such as a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy, and an electric tool. The vehicle can be a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle, or an extended-range vehicle, etc.; the spacecraft includes an airplane, a rocket, a space shuttle, and a spacecraft, etc.; the electric toy includes a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc.; the electric tool includes a metal cutting electric tool, a grinding electric tool, an assembly electric tool, and a railway electric tool, such as an electric drill, an electric grinder, an electric wrench, an electric screwdriver, an electric hammer, an impact drill, a concrete vibrator, and an electric planer, etc. The embodiments of the present application do not impose any special restrictions on the above-mentioned devices.

[0068] The following are specific embodiments of the present application, and the technical scheme of the present application is further described in conjunction with the embodiments, but the present application is not limited to these embodiments. The reagents, methods and equipment used in the present application, unless otherwise specified, are conventional reagents, methods and equipment in the art.

[0069] Example 1

[0070] Provided is a negative electrode material, wherein a method for preparing the negative electrode material specifically comprises the following steps:

[0071] Petroleum coke with a sulfur content of 3% is selected as raw material, and is shallowly calcined at a temperature of 600°C, and then crushed and dried to obtain coarse powder; the coarse powder is placed in a high-temperature furnace and heated to 3000°C at a heating rate of 10°C / min under an argon inert atmosphere for high-temperature graphitization treatment for 24 hours to obtain a single-particle graphitized product, and the obtained single-particle graphitized product is sieved and demagnetized to obtain a finished product.

[0072] Examples 2 to 17, Comparative Examples 1 to 3

[0073] A series of negative electrode materials are provided, which are prepared by referring to the method of Example 1. By changing the sulfur content, heating rate, graphitization temperature, processing time and other parameters in the petroleum coke raw material in Example 1, negative electrode materials with different physical properties are obtained. The parameters of the obtained negative electrode materials are detailed in Table 1.

[0074] Regarding the physical properties of the above negative electrode materials:

[0075] 1) In this application, the particle size of the negative electrode material (including D V 90.D V 50. D V 10, unit is μm) was tested by a particle size tester, and the specific results are shown in Table 1;

[0076] 2) In the present application, the Raman spectrum test conditions of the negative electrode material are as follows: exposure time 0.5s, cumulative number of 2500 points, objective lens magnification 100 times, and the test results are detailed in Table 1;

[0077] 3) Powder compaction density of negative electrode material (in g / cm 3 ): The compaction density of the powder under 3T is recorded as Q, and the test parameters are: pressurization speed 8mm / min, pressurization to 30kN and then hold the load for 30s, pressure relief speed 30mm / min, pressure relief to 20N and hold for 10s; the compaction density of the powder under 5T is recorded as Y, and the test parameters are: pressurization speed 8mm / min, pressurization to 50kN and then hold the load for 30s, pressure relief speed 30mm / min, pressure relief to 20N and hold for 10s;

[0078] 4) The specific surface area (BET) of the negative electrode material was measured using a specific surface area tester. The specific test results are shown in Table 1, in m 2 / g;

[0079] 5) Sulfur content (mass content): ICP-OES equipment is used to perform elemental analysis to test the sulfur content of the material. The specific test conditions are:

[0080] Sample weight: 0.4 g; Digestion method: microwave digestion; Digestion acid and volume: 12 mL aqua regia; Fixed volume: 100 mL;

[0081] 6) Graphitization degree G (unit: %): PANalytical Empyrean equipment was used to test the graphitization degree of the material. Test conditions: copper target was used as the target material, voltage and current were 45 kV, 40 mA, test angle was 24° to 30°, and test step length was 0.01° , Silicon-carbon ratio 1.5:3.5;

[0082] The test results are shown in Table 1.

[0083] Table 1

[0084]

[0085] Table 1 (continued)

[0086]

[0087] The negative electrode materials prepared in the above examples and comparative examples were prepared into secondary batteries, and then the electrochemical performance of the secondary batteries was tested.

[0088] The preparation of the secondary battery includes the following steps:

[0089] Positive electrode preparation

[0090] The positive electrode active material NCM622, the conductive agent SP (conductive carbon black), the additive CNT (carbon nanotube), and the binder PVDF were mixed in a mass ratio of 96.3:1.9:0.5:1.3, and the solvent NMP was added. After stirring evenly under the action of a vacuum mixer, a positive electrode slurry was obtained; the positive electrode slurry was evenly coated on the positive electrode current collector aluminum foil by transfer coating to form a positive electrode active material layer, and then dried at a temperature of 100±10℃, and a positive electrode sheet was obtained by rolling and cutting. The thickness of the positive electrode active material layer was 96μm, and the compaction density was 3.4g / cm 3 ;

[0091] Negative electrode preparation

[0092] The negative electrode material, conductive agent carbon black, binder styrene-butadiene rubber and additive sodium carboxymethyl cellulose prepared in the above embodiments and comparative examples were mixed in a mass ratio of 96.5:0.7:1.8:1.0, and deionized water was added as a solvent. The mixture was stirred evenly under the action of a vacuum mixer to obtain a negative electrode slurry. The negative electrode slurry was evenly coated on the negative electrode current collector copper foil by transfer coating to form a negative electrode active material layer, and then dried at a temperature of 80±10°C, and rolled and cut to obtain a negative electrode sheet, wherein the thickness of the negative electrode active material layer was 121 μm. At the same time, the compaction density of the negative electrode sheet was recorded. The specific test results are shown in Table 3.

[0093] Electrolyte preparation

[0094] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain a mixed organic solvent, and then LiPF6 is dissolved in the mixed organic solvent, and after mixing evenly, an electrolyte with a lithium ion concentration of 1 mol / L is obtained;

[0095] Assembly of secondary batteries

[0096] The prepared positive electrode sheet, separator (polypropylene separator, Celgard 2300, purchased from Celgard, USA), and negative electrode sheet are stacked in order so that the separator is between the positive and negative electrode sheets, and then wound to obtain a bare battery cell, which is then loaded into a soft-pack shell. After top and side sealing, liquid injection (electrolyte), formation, sorting and other processes, a lithium-ion secondary battery is obtained.

[0097] The performance test of secondary batteries is as follows:

[0098] 1) Negative electrode lithium deposition: The lithium-ion secondary battery was placed at 25°C for 30 minutes, charged to 4.4V at 2.2C constant current, placed for 30 minutes, discharged to 2.8V at 1C constant current, and placed for 10 minutes. After 10 charge and discharge cycles, the lithium-ion battery was charged to 4.4V at 2.2C constant current, and stopped after 10 minutes of standing. The battery was disassembled to observe the interface condition of the negative electrode. Specifically, the disassembled negative electrode interface was placed under an electron microscope. According to the proportion of lithium deposition area (expressed by S), the degree of lithium deposition was divided into the following levels (see Table 2):

[0099] Table 2

[0100] Interface lithium deposition area ratio Corresponding level Lithium precipitation degree S≤2% 0 No lithium precipitation 2%<S≤20% I Slight lithium deposition 20%<S≤40% II Moderate lithium precipitation 40%<S≤60% III Severe lithium deposition

[0101] 2) Gram capacity test: Assemble in the order of “button positive electrode cover - gasket - membrane - electrolyte - diaphragm - electrolyte - lithium sheet - filler - button negative electrode cover” and place in a glove box with argon atmosphere. Before testing, the assembled button cell is allowed to stand for 3 to 4 hours to allow the electrolyte to fully infiltrate the electrode plate to obtain a button half-cell, wherein the preparation method of the negative electrode plate of the button half-cell is as follows: mix according to the ratio of negative electrode material: SP: CMC: LA133 = 94.5: 1.5: 1.5: 2.5, then stir for 30 minutes, evenly apply the slurry on the negative electrode copper foil with a scraper, and then vacuum dry the negative electrode plate at 105°C for more than 2 hours to prepare the negative electrode plate of the button half-cell. The button half-cell was used to test the gram capacity of the negative electrode material. The specific test steps were as follows: 0.05C discharge to 5mV, stand for 5 minutes, 0.05mA discharge to 5mV, stand for 5 minutes, 0.01mA discharge to 5mV, and then 0.1C charge to 2V. The charge capacity at this time is the gram capacity of the negative electrode material, in mAh / g.

[0102] 3) Cycle performance: Place the secondary battery in a charge and discharge test cabinet, perform a 45°C constant temperature cycle test (0-97% SOC), charge to 4.35V at 1C constant current and constant voltage, and set the cut-off current at 0.05C; let stand for 30 minutes, then discharge to 2.8V at 1C constant current, and let stand for 10 minutes; this is a charge and discharge cycle process, and the cycle charge and discharge are repeated. When the cycle capacity retention rate is ≤80%, stop the test, and record the first discharge capacity and the number of cycles when the test is stopped;

[0103] 4) Rate performance: The secondary battery was placed in a charge and discharge test cabinet, at a constant temperature of 25°C, charged to 4.2V at 1C constant current and constant voltage, with a cut-off current of 0.05C, and allowed to stand for 30 minutes, then discharged to 2.8V at 0.33C constant current, and then charged to 4.2V at constant current and constant voltage each time, allowed to stand for 30 minutes, and discharged at 0.33C, 0.5C, 1C, 2C, 3C, and 4C respectively, and the capacity at different rates was recorded, respectively recorded as C1, C2, C3, C4, C5, and C6, and the capacity retention rate after cycling at different rates = (C6 / first discharge capacity)*100% was calculated.

[0104] The test results are shown in Table 3:

[0105] Table 3

[0106]

[0107] From the above results, we can see that:

[0108] By matching the relationship between the half-width of the G peak of the negative electrode material and the compaction density of the negative electrode material powder under pressures of 3T and 5T, a secondary battery with both high energy density and cycle performance is prepared.

[0109] Among them, the gram capacity of the negative electrode materials prepared in the present application is above 354 mAh / g. The obtained batteries are cycled under 45°C, 1C / 1C charge and discharge conditions, and the number of cycles when the capacity retention rate reaches 80% is above 1200 cycles; the capacity retention rate at 4C rate is above 85%.

[0110] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A negative electrode material, characterized in that: The negative electrode material includes a carbonaceous material, and the negative electrode material satisfies the following relationship: 12.0≤2×(YQ)+1.5×Gh≤60.5 Where, Gh cm -1 Indicates that the negative electrode material has a displacement of 1580±10cm in the Raman spectrum -1 The half-peak width of the G peak at position; Y g / cm 3 Indicates the powder compaction density of the negative electrode material under a pressure of 5T; Q g / cm 3 It represents the powder compaction density of the negative electrode material under a pressure of 3T.

2. The negative electrode material according to claim 1, characterized in that: The negative electrode material satisfies the following relationship: 20.0≤2×(YQ)+1.5×Gh≤50.

0.

3. The negative electrode material according to claim 1, characterized in that: The half peak width Gh of the negative electrode material in the Raman spectrum satisfies: 8 cm -1 ≤Gh≤40cm -1 .

4. The negative electrode material according to claim 1, characterized in that: The powder compaction density Y of the negative electrode material under 5T pressure satisfies: 1.800g / cm 3 ≤Y≤1.900g / cm 3 .

5. The negative electrode material according to claim 1, characterized in that: The powder compaction density Q of the negative electrode material under 3T pressure satisfies: 1.600g / cm 3 ≤Q≤1.700g / cm 3 .

6. The negative electrode material according to claim 1, characterized in that: The negative electrode material satisfies at least one of the following characteristics: (1) The specific surface area BET of the negative electrode material satisfies: 0.5 m 2 / g≤BET≤2.7m 2 / g; (2) The graphitization degree G of the negative electrode material satisfies: 92%≤G≤95%.

7. The negative electrode material according to claim 1, characterized in that: The negative electrode material satisfies at least one of the following characteristics: (1) When the cumulative volume of the negative electrode material reaches 90%, the corresponding particle size is D V 90, satisfying: 20μm≤D V 90≤50μm; (2) When the cumulative volume of the negative electrode material reaches 50%, the corresponding particle size is D V 50, satisfying: 10μm≤D V 50≤20μm; (3) When the cumulative volume of the negative electrode material reaches 10%, the corresponding particle size is D V 10, meet: 5μm≤D V 10≤12μm; (4) The negative electrode material satisfies: 1.5≤(D V 90-D V 10) / D V 50≤2.

0.

8. The negative electrode material according to claim 1, characterized in that: The negative electrode material satisfies at least one of the following characteristics: (a) The gram capacity of the negative electrode material is ≥354 mAh / g; (b) The sulfur content of the negative electrode material is ≤0.01 wt%.

9. A secondary battery comprising a positive electrode sheet, an electrolyte, a separator and a negative electrode sheet, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises the negative electrode material according to any one of claims 1 to 8.

10. An electrical device, characterized in that: The electric device comprises the secondary battery according to claim 9.

Citation Information

Patent Citations

  • Silicon oxide / carbon composite anode material and preparation method thereof and lithium ion battery

    CN112018334A

  • Negative active material, negative pole piece, preparation method and application

    CN113594451A

  • Negative electrode material and battery

    CN115954472A

  • Negative active material, negative pole piece, secondary battery and electronic device

    CN117059763A

  • High-nickel ternary positive electrode material, preparation method thereof and lithium ion battery

    CN117334860A